Oscillatory regularity of charge carrier traps energy spectra in silicon organic polymer poly(di-n-hexylsilane) - Gumenjuk, A.; Ostapenko, N.; Ostapenko, Yu.; Kerita, O.; Suto, S.; Watanabe, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Charge carrier traps energy spectra have been investigated in silicon organic polymer poly(di-n-hexylsilane) by fractional thermally stimulated luminescence in the temperature range from 5 to 200 K. The energy spectrum of traps has been found to be discrete in nature, not the quasi-continuous, as it was considered earlier. It has been established that the traps energies form two characteristic series resulting from the vibrational quanta at 373 and 259 cm–1, respectively. It is important that these vibrational quanta coincide with the frequencies of the totally symmetric vibrational modes of silicon chain which are active in Raman spectrum. The regularities mentioned are analyzed using the oscillatory traps model as the basis.